The Effect of Online Learning on Mathematics Value of Seventh Class Students in Bulu China Swadaya SMPS - Irwan Irwan; Mardiati Mardiati; Lilis Saputri; Seget Tartiyoso; Efrini Panjaitan (Journal of Social Science, 2021)
This study aims to determine (1) learning outcomes in mathematics, (2) the effect of WhatsApp media on students' mathematics learning outcomes. This research is quasi-experimental. The population in this study were students of class VII SMP, totaling 36 students. In this study, the sample used was total sampling in which all populations were sampled in this study. The design used in this study was the pre-test post-test control group design. The research instrument was a learning outcome test and a learning difficulty questionnaire. To test the hypothesis using a paired sample t-test. The results of this study indicate that the post-test mean score that has been tested in the experimental class is 83.50. This means that the learning outcomes in the experimental class are seen by using the paired sample t-test of 0.006 <0.05, which means that there is a significant effect between the average value before treatment (pre-test) and the average value after treatment (post-test).